Other # Metoo (New York OUP, 2023)
From Asia to Africa to the Middle East, #MeToo has inspired local movements and hashtag trends like #AnaKaman and transnational collective hashtags like #MosqueMeToo. Yet, most Western scholarly and popular treatment of the movement assumes it is a primarily Western phenomenon. To attend to the revolutionary international impact of #MeToo, Iqra Shagufta Cheema brings together contributions from scholars and scholar activists that look at specific iterations of the #MeToo movement across multiple communities, cultures, and countries in the Global South. Going beyond gender, this comprehensive study focuses on the intersectional assemblage of ethnicity, religion, race, class, and politics that informs #MeToo and its place in local and transnational feminisms. By doing so, The Other #MeToos highlights the adaptation, translation, and impact of #MeToo in non-Western, postcolonial, minoritized, and othered locales to explore its wider scope and possibilities.
Keywords: Social Sector; Sociolism; Women Harrasment; Gender discrimination; Cheema, Iqra Shagufta ed